2012
DOI: 10.5812/jjm.4569
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Genotyping of Human Papillomavirus in Cervical Tissue Samples in Ahvaz, Southwest Iran

Abstract: Background: 500,000 new cases with progressive cancer of cervix are reported worldwide annually. This malignant cancer is the second common cancer among females. Human papillomavirus (HPV) is considered as the major cause of cervical cancer and dysplasia. PCR Application to detect the HPV DNA in clinical specimens besides microscopic examination of cervical biopsy (Papanicolaou smear) (Pap smear) are valuable prognostic indicators in cervical cancer management. Objectives: Due to the absence of epidemiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…To a certain extent, this finding is consistent with the type of variants present in West African region, with genotypes 16 and 18, regarded as the most common variants of HPV available worldwide ( 8 ). Hamidi-Fard et al ( 9 ) also reported that the most prevalent HPV in their study, in Iran, was HPV 16. Results showed a 100% presence of high risk HPV in all the samples with abnormal cytology, which would have not been known via the conventional PAP test.…”
Section: Discussionmentioning
confidence: 74%
“…To a certain extent, this finding is consistent with the type of variants present in West African region, with genotypes 16 and 18, regarded as the most common variants of HPV available worldwide ( 8 ). Hamidi-Fard et al ( 9 ) also reported that the most prevalent HPV in their study, in Iran, was HPV 16. Results showed a 100% presence of high risk HPV in all the samples with abnormal cytology, which would have not been known via the conventional PAP test.…”
Section: Discussionmentioning
confidence: 74%
“…In a study published by Zandi et al, in 2010, the prevalence of HPV-16 genotype was almost 64% in the south of Iran (17). In a similar survey, which had been done by Hamidi -Fard et al, in 2012, 50% of the positive samples were genotype 16 (12). According to these studies, it may be reported that HPV-16 genotype is the most common HPV genotype in Iran; however, this conclusion needs more studies surely.…”
Section: Discussionmentioning
confidence: 88%